Does the Sharia-compliant Status Removal Announcement Matter? Liquidity, Trading Activities and Institutional Investors - Rozaimah Zainudin,; Karren Lee-Hwei Khaw, (Asian Academy of Management Journal of Accounting and Finance, 2024)
On 29th November 2013, the Security Commission Malaysia revised the Sharia-compliant screening policy and about 20% of the Sharia firms lost their certification for not meeting the additional criteria. Using 107 affected firms, we examine the removal announcement effect on the stocks’ liquidity and trading activities. Our analysis focuses only on the removal announcement due to the screening policy changes. We use 181 days event window for the short-term effect and multivariate panel estimation models for the long-term effect. The event study observes a decreasing trend for the liquidity measures, indicating a higher liquidity post-Sharia removal announcement among the affected stocks. Conversely, trading activities decrease substantially within the first few days post-event date before picking up gradually. The regression analysis confirms the results, but we do not find consistent results supporting the relationship between institutional investors and liquidity and trading activities. The study is among the pioneers to unfold the effect of Sharia-compliant status removal announcement due to the policy changes on the stock liquidity and trading activities within short and long-term perspectives. We also provide post-effect evidence on the change of the institutional investors due to the removal announcement on the liquidity and trading aspect.